E-Module in TVET: unveiling brazing and riveting methods through VAK learning - Hashim, Suhaizal; Mohamad Ali, Nur Alianni; Masran, Saiful Hadi (2023)
The electronic module (e-module) concern within the realm of Technical and Vocational Education and Training (TVET) pertains to the obstacles related to the incorporation and proficient utilization of electronic learning resources in vocational education systems. The issues discussed involve several factors, including insufficient digital infrastructure, restricted technological accessibility, differing degrees of digital literacy among educators and learners, and the necessity for comprehensive training and assistance to facilitate the smooth integration of e-module. This research focuses on the creation of an educational e-module for vocational colleges, specifically targeting the refrigeration and air conditioning program. The instructional material is designed to cater various learning styles, including visual, auditory, and kinesthetic (VAK) approaches. The purpose of this e-module is to facilitate the acquisition of knowledge for both teachers and students through the utilization of highquality reference materials for the Fabrication of Piping, Tubing, and Metal topics. The researcher employed a semi-structured interview as the research instrument to evaluate the usability of the learning e-module in this study. Subsequently, the interview data will undergo thematic analysis and subsequently be assessed using Cohen's Kappa statistic, which will ascertain the level of agreement over the usefulness of the e-learning module. The findings of this study indicate that the e-module created possesses attributes of interest and suitability, rendering it a viable resource for reference purposes. The development of this learning emodule is anticipated to yield benefits for both instructors and students in the teaching and learning process